2015
DOI: 10.1155/2015/497056
|View full text |Cite
|
Sign up to set email alerts
|

CD69 Is the Crucial Regulator of Intestinal Inflammation: A New Target Molecule for IBD Treatment?

Abstract: CD69 has been identified as an early activation marker of lymphocytes. However, recent work has indicated that CD69 plays an essential role for the regulation of inflammatory processes. Particularly, CD69 is highly expressed by lymphocytes at mucosal sites being constantly exposed to the intestinal microflora (one of the nature's most complex and most densely populated microbial habitats) and food antigens, while only a small number of circulating leukocytes express this molecule. In this review we will discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 137 publications
(198 reference statements)
2
36
0
1
Order By: Relevance
“…Engagement of CD69 can activate NK and T cells, resulting in the upregulated cytotoxic activity and pro-inflammatory cytokines secretion (Sancho et al, 2005).Owing to the absence of a known ligand, the biological function and underlying mechanisms of CD69 have not been extensively studied. In recent years, CD69 has been reported as the negative regulating factor for the T cell response because CD69-deficient mice develop more severe T cell-mediated autoimmune diseases, meanwhile, CD69 deficiency could promote the antitumor response (Radulovic and Niess, 2015;Wieland and Shipkova, 2016). Furthermore, CD69 engagement can not only induce apoptosis in monocytes and eosinophils, and also suppress IL-1 receptor-or CD3-mediated T cell proliferation (Ramírez et al, 1996;Walsh et al, 1996;Cosulich et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Engagement of CD69 can activate NK and T cells, resulting in the upregulated cytotoxic activity and pro-inflammatory cytokines secretion (Sancho et al, 2005).Owing to the absence of a known ligand, the biological function and underlying mechanisms of CD69 have not been extensively studied. In recent years, CD69 has been reported as the negative regulating factor for the T cell response because CD69-deficient mice develop more severe T cell-mediated autoimmune diseases, meanwhile, CD69 deficiency could promote the antitumor response (Radulovic and Niess, 2015;Wieland and Shipkova, 2016). Furthermore, CD69 engagement can not only induce apoptosis in monocytes and eosinophils, and also suppress IL-1 receptor-or CD3-mediated T cell proliferation (Ramírez et al, 1996;Walsh et al, 1996;Cosulich et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is an leukocytic early activation marker [47]. Interestingly this protein like L-Plastin has been found in circulating leukocytes and is presence in intestinal mucosa where by it functions in an inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly this protein like L-Plastin has been found in circulating leukocytes and is presence in intestinal mucosa where by it functions in an inflammatory role. It has been suggested to play a role in preventing bacterial pathogens from crossing the external layers of mucosa into the deeper inner tissues [47]. CD69 is expressed in memory T cells and regulatory T cells, in intestinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies performed in in vitro conditions, reported inhibitory effects of dopamine on fMLPstimulated superoxide anion production by human neutrophils [34]. Dopamine has also been reported to attenuate CD11b/CD18 expression in neutrophils, with consequently diminished ability of human neutrophil adherence to the endothelium, as well as a decrease in the production of ROS and superoxide anions, cell migration and phagocytic activity [35].…”
Section: Fig 2 Clinical and Macroscopic Features Of Iodoacetamide-imentioning
confidence: 99%